Expression of PKCι/YAP1 in Cervical Cancer and Its Clinical Significance - CHEN Shengmin (Magazine House of Cancer Research on Prevention and Treatment, 2021)
Objective To investigate the role of PKCι, YAP1 and high-risk HPV infection in the local immune microenvironment of cervical cancer. Methods We chose 80 cases of normal tissue of the cervix (NCT), cervical low-grade squamous intraepithelial lesion (LSIL), cervical high-grade squamous intraepithelial lesion (HSIL) and early cervical squamous cell carcinoma (SCC) each. Four groups were collected.The infection rate of high-risk HPV in four groups was determined by real-time fluorescence PCR method. The expression levels of PKCι, YAP1, CD4 and CD8 in four groups were measured and correlated by IHC and clinicopathologic features were also analyzed. Results The differences of high-risk HPV infection rate and PKCι, YAP1, CD4, CD8 positive rate among groups of NCT, LSIL, HSIL and SCC had statistical significance (P < 0.05). The level of cervical lesions was positively associated with high-risk HPV infection and positive PKCι, YAP1, CD8 expression (P < 0.05), while negatively associated with positive CD4 expression (P < 0.05). HPV infection and positive PKCι, YAP1, CD8 expression were positively correlated with each other in SCC, while were all negatively correlated with positive CD4 expression(P < 0.05). The differences of HPV infection, PKCι, YAP1 and CD8 positive expression were significant in different levels of differentiation and vascular invasion of SCC (P < 0.05). Conclusion The patients with cervical lesions are often accompanied by high-risk HPV infection and abnormal expression of PKCι, YAP1, CD4 and CD8, which may have synergistic effects on each other, causing the local immunosuppression microenvironment of SCC. It provides a possible strategy for the study of pathogenesis, diagnosis and treatment of cervical cancer.